Studying the effect of alumina on the mechanical properties of aluminum alloy prepared from waste using powder metallurgy - Hussien Omran, Salman; H. Ali, Moaz; Mohsen Mottar Al-Masoudy, Murtadha; Abed Hajer, Muatamed (International Journal of Engineering and Technology, 2019)
Nowadays, there is an increasing request worldwide for the advanced materials so as to get the preferred properties. This is for the reason that a particular material normally cannot meet the requirement of severe engineering environment that is why the need for composites arises. Metal matrix composite is a- main class of materials with high potential for structural applications needing high specific modulus, strength and toughness. Metal matrix composites with unique properties are growing every day and widely used in different industries because of their high mechanical properties and wear resistance. The mechanical and physical tests carried out in this work involve hardness, wear rate, microstructure, and XRD. The results showed that there was an improvement in mechanical properties of the composite which was achieved by adding ceramic reinforcement phase. In comparison with the base metal.Â Â Â